Naïve CD4 T cells inhibit CD28-costimulated R5 HIV replication in memory CD4 T cells - Mengozzi, Manuela (The National Academy of Sciences, 2001)
Stimulation with antibodies to CD3 and CD28 coimmobilized on beads can be used to significantly expand T cells ex vivo. With CD4 T cells from HIV-infected patients, this expansion usually is accompanied by complete suppression of viral replication, presumed to be caused by down-regulation of the viral coreceptor CCR5 and up-regulation of CCR5 ligands. Here we show that this suppression occurs in total CD4 T cells acutely infected with R5 HIV, but not in purified CD62L(−) memory CD4 T cells. The lack of complete suppression in these memory cells, typically comprising 10–40% of total CD4 T cells, occurs despite high levels of CCR5 ligand secretion and down-regulation of CCR5. Significantly, adding back naïve or CD62L(+) memory CD4 T cells inhibits the viral replication in the CD62L(−) cells, with the naïve cells capable of completely repressing the virus. Although this inhibition was previously thought to be specific to bead-bound anti-CD3/CD28 stimulation, we show that the same suppression is obtained with sufficiently strong anti-CD3/B7.1 stimulation. Our results show that inhibitory mechanisms, expressed predominantly by strongly stimulated naïve CD4 T cells and mediated independently of CCR5-binding chemokines, play a role in the inhibition of R5 HIV replication in CD4 T cells upon CD28 costimulation.